The landscape of proper names and Polish-French linguistic contacts in the 17th century memoirs of François Paulin Dalairac - Zarębski, Rafał (Papers in Linguistics, 2022)
The article discusses the landscape of proper names, understood as a kind of linguistic landscape adapted to the purposes of diachronic linguistics. The research material for further considerations was excerpted from the 17th-century memoir of François Paulin Dalairac, a courtier to Jan III Sobieski. It has been concluded that old texts from the field of ego-documents (including memoirs) in which different languages appeared have a significant potential for the study of the concept of linguistic landscape and contacts. The primary language of the analysed memoirs is French, but there are also passages in other languages (mainly Polish), which may have played an important role in the learning and improvement of the author’s Polish.